2015
DOI: 10.1021/ma5024236
|View full text |Cite
|
Sign up to set email alerts
|

Polymer/Pristine Graphene Based Composites: From Emulsions to Strong, Electrically Conducting Foams

Abstract: The unique electrical, thermal, and mechanical properties of graphene make it a perfect candidate for applications in graphene/graphite based polymer composites, yet challenges due to the lack of solubility of pristine graphene/graphite in water and common organic solvents have limited its practical utilization. Here we report a scalable and environmentally friendly technique to form water-in-oil type emulsions stabilized by overlapping pristine graphene sheets, enabling the synthesis of open cell foams contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 34 publications
8
62
0
Order By: Relevance
“…This free energy change is lower than the corresponding 2.2 mN/m change of the free energy obtained for graphene displacement from an interface using similar calculations. 23,24 Using this value, we estimate the work required to displace BN sheets with 100 × 100 nm lateral dimensions from the water/ heptane interface into the heptane phase to be 4420 k B T. This energy is sufficiently strong to localize the BN sheet at the water/heptane interface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This free energy change is lower than the corresponding 2.2 mN/m change of the free energy obtained for graphene displacement from an interface using similar calculations. 23,24 Using this value, we estimate the work required to displace BN sheets with 100 × 100 nm lateral dimensions from the water/ heptane interface into the heptane phase to be 4420 k B T. This energy is sufficiently strong to localize the BN sheet at the water/heptane interface.…”
mentioning
confidence: 99%
“…This behavior is analogous to that observed for graphite in previous studies. 23,24 Because the BN sheets spread at the water wet hydrophilic glass surfaces of a vial that are in contact with an oil phase, they also climb the surface of glass slides placed in a vial. Figure 2A shows such a glass slide covered with a BN film.…”
mentioning
confidence: 99%
“…Due to accuracy and less intensive mathematical formulations, MD-based simulations are emerging as potential technique for investigating the nanomaterial's for the purpose of water desalination, enhancing impact strength of nanocomposites for armor grade materials, study involving the effect of radiation on nanomaterials, hydrogen storage, defect engineering, and developing biomaterials; yet challenges due to the lack of solubility of PG/BN in water and common organic solvents have somewhat limited its practical utilization. 216 The prime mechanism for the bonding to accomplish is largely due to the high surface-to-volume ratio of graphene and BN derivatives that tends to stretch the polymer chains and pack them along the graphene/BN nanofiller surface leading to a higher densification in vicinity of filler relative to the bulk. Studies have further revealed that the graphene/BN and their derivatives can form various noncovalent bindings to biomolecules and such interactions can lead to the secondary structural changes in the biomolecules and some innovative outcomes; forming the basis for nanobiocomposite materials.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Interestingly, in the recent decade, graphene has attracted considerable attention due to its distinguished electrical and magnetic behavior and excellent thermal and mechanical properties . Graphene nanoplate materials are typical 2D plate‐like materials with a high aspect ratio, good modulus, and heat conductivity; thus, it is used as reinforcement and conductive filler for polymer composites . Commonly, scholars have given a direct improvement strategy, that is, the functionalization of graphene nanoplates, to enhance compatibility between graphene materials and a variety of polymers .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Graphene nanoplate materials are typical 2D plate-like materials with a high aspect ratio, good modulus, and heat conductivity; thus, it is used as reinforcement and conductive filler for polymer composites. [20][21][22] Commonly, scholars have given a direct improvement strategy, that is, the functionalization of graphene nanoplates, to enhance compatibility between graphene materials and a variety of polymers. [23][24][25] Schvezov et al 26 blended PLA, thermoplastic cassava starch (TPCS), and functionalized graphene (GRH) by the reactive extruding process to obtain ternary PLA-g-TPCS-GRH composite, which exhibited better toughness compared with neat PLA.…”
Section: Introductionmentioning
confidence: 99%